2018
DOI: 10.1111/odi.12901
|View full text |Cite
|
Sign up to set email alerts
|

Role of oral examination in newly diagnosed multiple myeloma patients: A safe and simple way to detect light chain amyloidosis

Abstract: The salient feature of this study is the high prevalence of oral manifestations among MM patients with amyloidosis. These results highlight the value of routine oral cavity examination and biopsy as a safe and simple method for detecting light chain amyloidosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Penner et al [10] have reported that about 15% of patients with MM develop amyloidosis. Leiba et al [5] have evaluated 212 patients diagnosed with MM and of these, 6% were diagnosed with light chain amyloidosis, and 54% showed lesions in the oral cavity with amyloid deposits. No studies were identified where the manifestation of OA led to a diagnosis for the underlying disease, in this case, MM.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Penner et al [10] have reported that about 15% of patients with MM develop amyloidosis. Leiba et al [5] have evaluated 212 patients diagnosed with MM and of these, 6% were diagnosed with light chain amyloidosis, and 54% showed lesions in the oral cavity with amyloid deposits. No studies were identified where the manifestation of OA led to a diagnosis for the underlying disease, in this case, MM.…”
Section: Discussionmentioning
confidence: 99%
“…Also, some patients may be asymptomatic, being diagnosed through laboratory findings such as anemia, kidney disease, and high levels of proteins [2]. About 12% to 15% of MM patients develop amyloidosis during the course of the disease, although up to 30% have subclinical amyloid deposits [5]. Amyloidosis manifests itself as extracellular and irreversible deposition of amorphous and fibrillar proteins, known as amyloid, in different organs and tissues [6].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations